Keabsahan Tanda Tangan Elektronik Dalam Pelaksanaan Cyber Notary - Adrian F Harefa; Elwidarifa Marwenny; Helfira Citra (CV. ITTC INDONESIA, 2024)
Indonesia, which is in the era of globalization, is characterized by the era of Information and Communication Technology (ICT) which introduces the virtual world (cyberspace, virtual world) via the internet network, communication with paperless electronic media. Indonesian society has entered the virtual world which is abstract, universal, independent of the conditions of place and time through the media, and in today's developments, Notaries have also experienced technological advances as developments in society in carrying out their duties and functions as public officials, one of which is Electronic signature in Cyber Notary. In the provisions of Article 15 paragraph (3) of Law Number 2 of 2014, it is stated that other authorities regulated in statutory regulations include: authority to certify transactions carried out electronically (cyber notary), make deeds of waqf pledges and airplane mortgages, However, this provision is in conflict with Article 16 paragraph (1) letter m of Law Number 2 of 2014 which states that a Notary is obliged to read the deed in front of an audience in the presence of 2 (two) witnesses. Meanwhile, the cyber notary's position here is not directly in front of the Notary but through electronic means such as teleconference or video call, as well as Article 5 paragraph (4) in Law Number 11 of 2008, namely the provisions regarding electronic information and/or electronic documents which states that letters and documents which according to the law must be made in the form of a notarial deed or deeds made by deed-making officials must be made in written form, thereby giving rise to legal issues. The problem formulation includes 1). How to review the law regarding electronic signatures in notarial deeds based on Law Number 11 of 2008 concerning Electronic Information and Transactions and Law Number 2 of 2014 regarding amendments to Law Number 30 of 2004 concerning the Position of Notaries ; 2). What are the legal consequences of applying digital signatures in notarial deeds? To answer this question, a normative juridical approach is used, namely an approach through literature study by examining legislation related to the problem formulation. And based on the results of this research, it is concluded that certification of transactions using a cyber notary remains valid in accordance with Article 15 paragraph (3) of Law Number 2 of 2014 which gives notaries the authority to certify transactions using a cyber notary while still paying attention to the following elements. elements of an authentic deed in Law Number 2 of 2014 and Article 1868 of the Civil Code which are the authenticity of the deed, the authority to make the deed as well as reading and signing using a cyber notary in the notary's work area and the deed remains valid as long as the form of the deed complies with the provisions of Article 38 Law Number 2 of 2014 and article 1868 of the Civil Code and the Utilization of Internet Protocol addresses (IP addresses) serve as references for datagrams so that they can arrive and be received on the intended device in order to avoid abuse of authority outside the Notary's area of office.